2019
DOI: 10.1093/nar/gkz1070
|View full text |Cite
|
Sign up to set email alerts
|

Targeted PMP22 TATA-box editing by CRISPR/Cas9 reduces demyelinating neuropathy of Charcot-Marie-Tooth disease type 1A in mice

Abstract: Charcot-Marie-Tooth 1A (CMT1A) is the most common inherited neuropathy without a known therapy, which is caused by a 1.4 Mb duplication on human chromosome 17, which includes the gene encoding the peripheral myelin protein of 22 kDa (PMP22). Overexpressed PMP22 protein from its gene duplication is thought to cause demyelination and subsequently axonal degeneration in the peripheral nervous system (PNS). Here, we targeted TATA-box of human PMP22 promoter to normalize overexpressed PMP22 level in C22 mice, a mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
1
30
1
Order By: Relevance
“…route instead of intraperitoneal injection. In addition, our data are consistent with two recent studies showing that inhibiting PMP22 expression can ameliorate the neuropathological symptoms caused by PMP22 overexpression 50 , 51 . In contrast with our study, where siRNA was injected via i.v.…”
Section: Discussionsupporting
confidence: 92%
“…route instead of intraperitoneal injection. In addition, our data are consistent with two recent studies showing that inhibiting PMP22 expression can ameliorate the neuropathological symptoms caused by PMP22 overexpression 50 , 51 . In contrast with our study, where siRNA was injected via i.v.…”
Section: Discussionsupporting
confidence: 92%
“…As for other hereditary neuromuscular diseases in which gene therapy proved to be effective, the negative regulation of PMP22 expression represents the ideal biological endpoint and therapeutic goal (12)(13)(14). To date, in contrast to preclinical studies, clinical trials in CMT1A patients aimed to down-regulate PMP22 showed negative results (7,(15)(16)(17). Furthermore, gene therapy, in addition to the obvious technical difficulties, seems to be still poorly acceptable for CMT1A patients in which life expectancy and quality of life are not dramatically affected (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the protein expression of PMP22 can also be achieved by modulating the transcriptional activity of a gene. Recently, two independent research groups demonstrated the feasibility of PMP22 reduction by disrupting either the promoter or enhancer of PMP22 with gene editing technology [81,82]. The clustered regularly interspaced short palindromic repeats (CRISPR) and related Cas genes are now emerging as essential tools for gene editing [83,84].…”
Section: Modulation Of Transcriptional Activitymentioning
confidence: 99%
“…The in vivo efficacy of gene editing was evaluated by another group. Lee et al [82] targeted the TATA-box promoter of PMP22 to reduce the transcription. After intraneural delivery of CRISPR/ Cas9 protein targeting the TATA-box promoter of PMP22, the expression level of PMP22 in the sciatic nerve was effectively reduced in C22 mice.…”
Section: Modulation Of Transcriptional Activitymentioning
confidence: 99%
See 1 more Smart Citation